2014
DOI: 10.1371/journal.pone.0097043
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Anoxia-Induced Ethylene Response Factors That Interact with Promoters of Deastringency-Related Genes from Persimmon

Abstract: A hypoxic environment is generally undesirable for most plants and stimulates anaerobic metabolism. It is a beneficial treatment, however, for the removal of astringency from persimmon to improve the fruit quality after harvest. High soluble tannins (SCTs) content is one of most important causes of astringency. High CO2 (95%) treatment effectively reduced SCTs in both “Mopan” and “Gongcheng-shuishi” persimmon fruit by causing increases in acetaldehyde. Using RNA-seq and realtime PCR, twelve ethylene response f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 34 publications
(51 reference statements)
3
88
2
Order By: Relevance
“…mRNAs from twenty‐two DkERF genes were found to increase in abundance during deastringency treatment (high CO 2 ); however, only four, DkERF9/10/19/22 , have been shown previously to be involved in transcriptional regulation of anoxia‐related genes during persimmon fruit deastringency (Min et al ., , ). The possibility that other DkERF genes might also participate in fruit softening during astringency removal was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNAs from twenty‐two DkERF genes were found to increase in abundance during deastringency treatment (high CO 2 ); however, only four, DkERF9/10/19/22 , have been shown previously to be involved in transcriptional regulation of anoxia‐related genes during persimmon fruit deastringency (Min et al ., , ). The possibility that other DkERF genes might also participate in fruit softening during astringency removal was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two hypoxia‐responsive DkERF genes have been isolated from persimmon (Min et al ., , ; Yin et al ., ) and DkERF9/10/19/22 were shown to be involved directly in transcriptional regulation of anaerobic metabolism genes involved in persimmon deastringency (Min et al ., , ), but a possible role in postdeastringency fruit softening was not investigated. In the present research, a combination of high CO 2 storage and 1‐MCP treatment (together with CO 2 treatment) was shown to maintain fruit firmness while removing astringency, implicating some ERFs in the excessive postdeastringency softening.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-luciferase assay is widely used for trans-activation activity analysis of transcription factors (Hellens et al, 2005;Yin et al, 2010;Min et al, 2014). The EjNACs ORF were inserted in frame into the NotI and SpeI sites of pGreen II 0029 62-SK vector driven by the cauliflower mosaic virus 35S (CaMV35S) promoter.…”
Section: Dual-luciferase Assaymentioning
confidence: 99%
“…These authors suggested that this mode of modulation of ERFs is a fruit response to low temperature stress and is a factor in turning on ERFs and thus activating or repressing gene expression, which might be critical for fruit protection from stress damage during postharvest, and in our case could play an important role on the beneficial effect of the 3-day gaseous treatment at 0°C on table grapes. On the other hand, whereas the accumulation of ERF transcripts by low temperature has been previously described, the effect of high CO 2 levels on ERF expression has been analyzed only in kiwifruit (Yin et al, 2012), where the application of 5% of CO 2 at 20°C for up to 7 days activated the accumulation of several ERFs, and in persimmon (Min et al, 2014), where exposition to 95% of CO 2 during 1 day at 20°C, to remove astringency, induced the accumulation of most of the ERFs analyzed. To our knowledge, however, this is the first time that an induction of ERFs gene expression by the combination of high CO 2 levels and low temperature has been described in different reproductive organs and fruit tissues.…”
Section: Discussionmentioning
confidence: 99%